2023
DOI: 10.3389/fimmu.2023.1266792
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal homeostasis in the gut-lung-kidney axis: a prospective therapeutic target in immune-related chronic kidney diseases

Xinyin Liu,
Xiaoran Wang,
Peipei Zhang
et al.

Abstract: In recent years, the role of intestinal homeostasis in health has received increasing interest, significantly improving our understanding of the complex pathophysiological interactions of the gut with other organs. Microbiota dysbiosis, impaired intestinal barrier, and aberrant intestinal immunity appear to contribute to the pathogenesis of immune-related chronic kidney diseases (CKD). Meanwhile, the relationship between the pathological changes in the respiratory tract (e.g., infection, fibrosis, granuloma) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 215 publications
0
1
0
Order By: Relevance
“…Alterations in the gut microbiota might be sometimes beneficial for the CKD regression via the metabolic changes, immune modification, and/or reduced inflammation. Therefore, using prebiotics, probiotics, and/or fecal microbiota transplantation (FMT) to regulate the gut ecology may alleviate oxidative stress as well as improve kidney function [108]. (Figure 3) Remarkably, it has been reported that oral supplementation of short chain fatty acid may amend kidney functions in rats, possibly by enhancing autophagy/mitophagy via the AMPK/mTOR pathway [109].…”
Section: Another Tactic Regarding the Alteration Of Gut Microbiome Fo...mentioning
confidence: 99%
“…Alterations in the gut microbiota might be sometimes beneficial for the CKD regression via the metabolic changes, immune modification, and/or reduced inflammation. Therefore, using prebiotics, probiotics, and/or fecal microbiota transplantation (FMT) to regulate the gut ecology may alleviate oxidative stress as well as improve kidney function [108]. (Figure 3) Remarkably, it has been reported that oral supplementation of short chain fatty acid may amend kidney functions in rats, possibly by enhancing autophagy/mitophagy via the AMPK/mTOR pathway [109].…”
Section: Another Tactic Regarding the Alteration Of Gut Microbiome Fo...mentioning
confidence: 99%